The Role of Principals in Maintaining the Quality of Education Units: An Evaluation Study of Distance Learning Policies in Elementary Schools, Yogyakarta City - Wuri Wuryandani; Irfan Wahyu Prananto; Firmansyah Firmansyah; Amalia Rizki Ardiansyah; Kurniawati Kurniawati (Universitas Sebelas Maret, 2022)
The principal, as a leader, has a role and responsibility to improve the quality of education, especially in distance learning mode, which is prone to learning loss. The principal's paradigm is that the boss must change in the current era to become a servant to the school community. This is very much needed in improving the quality of managed education units. The purpose of this study is to describe the activities carried out by school principals in preparing for distance learning to obtain a policy on the evaluation seen. This study uses a qualitative descriptive approach, with data analysis using Miles and Huberman's steps. The research subject is the principal of the basic education unit in Yogyakarta. A total of 27 people. The results obtained, principals in elementary school education units in Yogyakarta have implemented distance learning following established guidelines. However, in the aspect of the care program, more action is still needed. Thus, in general, the conclusion is that the principal in the primary school education unit in the city of Yogyakarta has successfully implemented the existing guidelines.